Association of body mass index and waist circumference with major chronic diseases in Chinese adults - Jiachen, L; Jun, L; Meng, G; Yu, C; Guo, Y; Bian, Z; Pei, P; Du, H; Chen, J; Chen, Z; Li, L (China Medicine Association, 2019)
Objective To examine the association of BMI with major chronic diseases morbidity and all-cause mortality in Chinese adults.